Auditory evoked neuromagnetic response latency is associated with language ability in preschoolers with an elevated likelihood of intellectual or developmental disability - Chen, Yuhan; Young, Lauren; Kim, Mina; Watson, Shannon; Kaufman, Victoria; Beal, Bethany; Tuomi, Ilona; Wang, Bekah; McDonald-McGinn, Donna M.; Edgar, J. Christopher; Kuschner, Emily S.; Roberts, Timothy P. L. (Frontiers in Integrative Neuroscience, 2025)
IntroductionWe have shown that a delayed auditory cortex neural response is associated with language ability in school-age children with autism spectrum disorder and related syndromes, with this delay exacerbated in the context of co-occurring intellectual disability (ID). As a clinical diagnosis of ID is generally not made until school age, identification of neural measures that precede a behaviorally assessed ID diagnosis would help identify young children likely to benefit from early treatment. The present study evaluated if the speed of auditory cortex neural activity (M50 latency) would predict language ability in 3-year-old children who have an existing diagnosis that is a risk factor associated with a range of later functional outcomes, including ID or developmental delay (DD), irrespective of autism spectrum disorder diagnosis.MethodsThirty 3-year-old children with elevated likelihood for ID or DD (ID/DD-EL) were enrolled. Evaluable magnetoencephalography (MEG) data as well as language and cognitive ability measures were obtained from 23 participants.ResultsA longer time to encode auditory stimuli (i.e., a delayed M50 cortical evoked response) in the left hemisphere predicted lower language ability. Left M50 latency was not associated with cognitive ability. Right hemisphere M50 latency was not associated with language or cognitive ability.DiscussionPresent observations demonstrate that non-invasive brain imaging in conjunction with a passive auditory task (with early primary/secondary auditory cortex neural responses) can identify paths for variable language outcome in preschool children with ID/DD-EL. This lays the foundation for further investigation of these neural mechanisms as early indications for treatment as well as early signals of response to treatment.